Effect Of Plant Densities And Fertilizer Rates On Grain Yield Of Spring Maize In Inner Terai Condition (Agronomy Journal of Nepal, 2021)
To improve the yield of spring season maize in the inner terai of Nepal, the effect of increasing fertilizer levels for increasing planting densities on growth, yield attributes, and yield of open-pollinated maize variety were analyzed through the field experimentation in 2019. The treatments included factorial combinations of three planting densities, (a) 55556/ha, (b) 66667/ha, and (c) 83333/ha; and four fertilizers levels (research-based recommendation i.e., 120:60:40 N:P2O5:K2O kg/ha, 144:72:48 N:P2O5:K2O kg/ha, 180:90:60 N:P2O5:K2O kg/ha, and site-specific nutrient management (SSNM) based nutrient expert model recommendation i.e., 140:40:40 N:P2O5:K2O kg/ha) arranged in a split-plot design with three replications. Data on growth, yield attributes, and yield were analyzed by using R Studio. Growth was higher under the highest planting density and higher fertilizer levels applied treatments. The higher (p